Smart and sustainable power systems operations, planning, and economics of insular electricity grids - Catalão, João P. S. (CRC Press/Taylor & Francis Group, 2015)
The smart grid initiative, integrating advanced sensing technologies, intelligent control methods, and bi-directional communications into the contemporary electricity grid, offers excellent opportunities for energy efficiency improvements and better integration of distributed generation, coexisting with centralized generation units within an active network. A large share of the installed capacity for recent renewable energy sources already comprises insular electricity grids, since the latter are preferable due to their high potential for renewables. However, the increasing share of renewables